The war and the challenges of preserving cultural heritage in the border settlements of Aygehovit and Voskepar, Tavush region, RA - Kostandyan, Ani (History and Culture, 2025)
The article discusses the issue of cultural heritage, protection in border settlements of Tavush region of RA, as well as the new challenges emerging as a result of the concession of enclave lands, using the example of Aygehovit and Voskepar settlements. We referred to the conventions adopted by international organizations preventing damage to cultural heritage and to the international experience of how cultural values were damaged during wars.            As a result of the investigation, we came to the conclusion that in order to prevent new cultural genocides, stronger levers are needed to put pressure on the aggressor states.
Keywords: cultural heritage; challenges of cultural heritage protection; war; border heritage; enclaves; Tavush